The cultural criticism of Lewis Mumford and the creative city planning as an answer to the ecological crisis of modern civilisation - Kovács, Gábor (Creativity Studies, 2023)
The book of young Lewis Mumford (1895–1990) entitled Sticks and Stones: A Study of American Architecture and Civilization (first published in 1924) is a condensed version of his philosophy of city and a research program completed in his rich oeuvre. The title is telling: the starting point of Mumford is the idea that the architecture of a city is an objectified presentation of the value-system of the given civilisation. Stick and stones are not only sticks and stones: the material infrastructure is an embodiment of the values of civilisation, which are the basic motivating factors behind human actions. In other words: city is a mirror of civilisation; if the observer decodes the message encoded in sticks and stones, he/she gets the value-structure of the civilisation having produced the city. However, there is a mutual interdependence: human beings living in the city are not only passive possessors of a heritage determining one-sidedly their actions but they modify and restructure urban spaces: sticks and stones form our values, at the same time our values influence the concrete arrangement of sticks and stones. Creative city-planning is vital important. It gives possibility for the redirection of a civilisation’s future historical way. At the same time, creativity, in Mumford’s interpretation, does not mean the profit-generating capacity of the city; it has to serve the well-being of all citizens.